1996
DOI: 10.1046/j.1365-2249.1996.13702.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of plasma-soluble tumour necrosis factor receptors (TNF-R) in sarcoidosis

Abstract: SUMMARYTwo types of receptor for tumour necrosis factor-alpha (TNF-R), the 55-kD receptor (TNF-RI) and the 75-kD receptor (TNF-RII), have been identified. Soluble TNF-RI (sTNF-RI) and soluble TNF-RII (sTNF-RII) can be measured in culture supernatants and biological fluids, and the role of sTNF-R has been suggested. In the present study, we measured plasma sTNF-RI and sTNF-RII levels in 19 patients with active sarcoidosis by ELISA in order to assess the state of both types of receptors in this disease. Both pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Soluble TNF receptors (sTNF-R) may be capable of counteracting TNF-α effects [125]. In many pulmonary disorders including sarcoidosis elevated levels of sTNF-R are found in the BAL fluid [126] and increases in the plasma levels of these molecules correlating with disease activity have been observed [127]. Preliminary results obtained by the author's group demonstrate the presence of increased sTNF-R serum levels correlating with alveolar macrophage TNF-α release and this might, therefore, play a role in dampening the cachectin effects of TNF-α, as observed in a number of diseases [128].…”
Section: Alveolar Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Soluble TNF receptors (sTNF-R) may be capable of counteracting TNF-α effects [125]. In many pulmonary disorders including sarcoidosis elevated levels of sTNF-R are found in the BAL fluid [126] and increases in the plasma levels of these molecules correlating with disease activity have been observed [127]. Preliminary results obtained by the author's group demonstrate the presence of increased sTNF-R serum levels correlating with alveolar macrophage TNF-α release and this might, therefore, play a role in dampening the cachectin effects of TNF-α, as observed in a number of diseases [128].…”
Section: Alveolar Macrophagesmentioning
confidence: 99%
“…These molecules are released by alveolar cells [220,222] and elevated serum levels related to the clinical course are observed in active sarcoidosis and other chronic inflammatory disorders [221,[223][224][225][226]. BAL cell release and BAL fluid content of these cytokines do not correlate with their respective serum levels [221,224,227], which might be explained by the absence of a basal membrane leakage or only a limited defect of the basal membrane in sarcoidosis [228,229] and a release of these molecules in other compartments of the body with easier access to serum [221,224,230].…”
Section: Cytokine Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble forms of these receptors -sTNF-R55 and sTNF-R75 -appear to be shed from cells in response to TNF release, possibly to limit the activity of this cytokine [11]. TNF receptor levels are associated with disease severity in a number of inflammatory conditions [12][13][14]. In contrast to many other soluble receptors, it has been shown that the IL-6 signal may be delivered via binding to soluble IL-6 receptor (sIL-6R) and subsequent interaction of this complex with gp130 on the cell surface whether or not membrane-bound IL-6R is present [15].…”
Section: Introductionmentioning
confidence: 99%
“…The elevation of these cytokine inhibitors in serum/plasma and biological fluids in several diseases [24][25][26][27][28], and the inhibitory and protective effects of these cytokine inhibitors against IL-1-and TNF--mediated diseases, have been demonstrated [17,18,[29][30][31]. Although up-regulation of TNF-and IL-1 in bronchial asthma has been demonstrated, serum sTNF-R and IL-1Ra levels have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%